The Effect of Cost Sharing on an Employee Weight Loss Program: A Randomized Trial. Issue 1 (January 2018) - John, Leslie K.; Troxel, Andrea B.; Yancy, William S.; Friedman, Joelle; Zhu, Jingsan; Yang, Lin; Galvin, Robert; Miller-Kovach, Karen; Halpern, Scott D.; Loewenstein, George; Volpp, Kevin
Purpose: To test the effects of employer subsidies on employee enrollment, attendance, and weight loss in a nationally available weight management program. Design: A randomized trial tested the impact of employer subsidy: 100%; 80%, 50%, and a hybrid 50% subsidy that could become a 100% subsidy by attaining attendance targets. Trial registration: NCT01756066. Setting and Participants: Twenty three thousand twenty-three employees of 2 US companies. Measures: The primary outcome was the percentage of employees who enrolled in the weight management program. We also tested whether the subsidies were associated with differential attendance and weight loss over 12 months, as might be predicted by the expectation that they attract employees with differing degrees of motivation. Analysis and Results: Enrollment differed significantly by subsidy level ( P < .0001). The 100% subsidy produced the highest enrollment (7.7%), significantly higher than each of the lower subsidies (vs 80% subsidy: 6.2%, P = .002; vs 50% subsidy: 3.9%, P < .0001; vs hybrid: 3.7%, P < .0001). Enrollment in the 80% subsidy group was significantly higher than both lower subsidy groups (vs 50% subsidy: 3.9%, P < .0001; vs hybrid: 3.7%, P < .0001). Among enrollees, there were no differences among the 4 groups in attendance or weight loss. Conclusion: This pragmatic trial, conducted in a real-world workplace setting, suggests that higher rates of employer subsidization help individuals to enroll in weight loss programs, without a decrement in program effectiveness. Future research could explore the cost-effectiveness of such subsidies or alternative designs.